EFL Students’ Self-Regulation in Online Interactions with Lecturers and Peers - Nurvira Wardayani; Machdalena Vianty; Sofendi; Zahra Alwi; Didi Suhendi (Indonesian Journal Of Educational Research and Review, 2022)
Online learning is definitely advantageous in this current situation. Due to the technology, the teaching and learning process can continue despite the students and instructor/lecturer located in different places. This study aims to understand student’s self-regulation in online learning particularly for interactions with their lecturer and their peers. To answer the research objectives, qualitative method with narrative approach was applied. The data were collected through open-ended questionnaire focused on self-regulation in online interactions with lecturers and peers. The participants in this study were 12 students from English Education Study Program. The data were analyzed by using thematic analysis. The results revealed that students did not notice a significant difference between face-to-face learning and online learning. They regularly interacted with their lecturer and their peers during synchronous and asynchronous learning. They actively initiated the interactions with their lecturer by asking or answering questions and giving opinions. They also actively interacted with peers by discussing academic projects and assignments. Regardless of the type of interactions (student-lecturer and student-student), most of the students showed their active efforts in regulating their interactions with lecturer and peers in online learning.